Special Preschools Monitoring a Pilot Project. Volume I: Project Report - Hayes, A.; Queensland Univ., Brisbane (Australia). Fred and Eleanor Schonell Educational Research Centre ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
A project was developed for the purpose of monitoring the special education program of the Queensland, Australia, Department of Education. This program offered educational support for very young handicapped children and their families. The monitoring team had a formative role in providing the services of consultants to advise teachers in certain areas of program development and a research role in documenting the development of four specific preschool programs over the 2-year pilot period. Questionnaires, interviews, observations, written submissions, workshops, seminars, consultations, and formal assessments were employed. Central attention was paid to the children, their families, the staff most closely associated with children and families, and the program that was developed to meet existing needs. Attention was also directed toward examinations of the roles of guidance officers, school medical officers, other professionals, teachers in regular preschools and kindergartens, and, finally, other organizations and agencies. Discussion of the data begins with a description of the contexts of early educational intervention and then progresses to an overview of the four programs, the support services available to them, and programs beyond those undertaken in the special preschools. The final chapter summarizes key issues and makes specific recommendations for future program development. (RH)
Sponsoring Agency: Queensland Dept. of Education, Brisbane (Australia).
ERIC Note: For related document, see ED 236 822.
Educational level discussed: Kindergarten.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Down Syndrome; Family Characteristics; Foreign Countries; Formative Evaluation; Handicap Identification; Kindergarten; Mainstreaming; Physical Examinations; Pilot Projects; Preschool Children; Preschool Education; Program Descriptions; Program Design; Program Development; Psychomotor Skills; Services; Special Education; Student Placement; Teacher Role; Australia (Queensland); Program Monitoring; Reports, Descriptive